CELEBRITY ENDORSEMENTS: A STUDY ON THEIR INFLUENCE ONCONSUMER BRAND PREFERENCE FOR HOME APPLIANCES (International Journal of Food and Nutritional Sciences, 2022)
Celebrity endorsements play a crucial role in shaping consumer brand preferences,particularly in the home appliance sector. By leveraging the trust, credibility, and emotionalconnections that celebrities have with their audiences, brands can enhance their visibility andperceived quality. This paper explores the mechanisms through which celebrity endorsementsinfluence consumer behaviour and examines case studies of successful endorsements.